2003
DOI: 10.1213/01.ane.0000068881.01031.09
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Three Different Concentrations of Levobupivacaine for Caudal Block in Children

Abstract: The use of 0.125% levobupivacaine for caudal blockade (1 mL/kg) in children (1-7 yr) was associated with less early postoperative motor blockade but a shorter duration of postoperative analgesia compared with 0.20% and 0.25% solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
1
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 17 publications
2
35
1
5
Order By: Relevance
“…In previous studies, bupivacaine produced a significant incidence of residual motor block after caudal block compared with levobupivacaine or ropivacaine [14,21]. Also, we did not observe residual motor blockade neither in group levobupivacaine-morphine nor in group levobupivacaine in our study.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…In previous studies, bupivacaine produced a significant incidence of residual motor block after caudal block compared with levobupivacaine or ropivacaine [14,21]. Also, we did not observe residual motor blockade neither in group levobupivacaine-morphine nor in group levobupivacaine in our study.…”
Section: Discussioncontrasting
confidence: 58%
“…We used levobupivacaine 0.25% with bolus epidural injection or 0.125% levobupivacaine-morphine combination and total volume was limited 0.7 ml/kg. Ivani et al [14] investigated three different concentration levobupivacaine (0.125%, 0.20% and 0.25% in each group) for caudal blockade in a undergoing subumbilical surgery. They found that the use of 0.125% levobupivacaine for caudal blockade in children was associated shorter duration of postoperative analgesia compared to 0.20% and 0.25% concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter contains the latest spinal roots forming the cauda equina and the filum terminal. Levobupivacaine is widely used clinically in caudal and spinal anesthesia [2,4] to manage acute and chronic pain. It acts on pain by inhibiting the activity of NMDA receptors (N Methyl D Aspartate) in the dorsal horn of the spinal cord [16].…”
Section: Discussion Limitation Of the Studymentioning
confidence: 99%
“…Ivani et al had studied three different concentration of caudal levobupivacaine 1 ml/kg (0.125%, 0.2%, and 0.25%) without additives in children and they found that 0.125% concentration was associated with significantly less motor blockade than that with other concentration but also had significantly shorter duration of postoperative analgesia than that with levobupivacaine 0.2% or 0.25% [21] so if levobupivacaine is used without additives, it should be used in high concentration to ensure good quality of postoperative analgesia.…”
Section: Discussionmentioning
confidence: 99%